Optimizing the Region for Evaluation of Global Gamma Analysis for Nasopharyngeal Cancer (NPC) Pretreatment IMRT QA by COMPASS: A Retrospective Study - Lu, Wenli; Li, Ying; Huang, Wei; Cui, Haixia; Zhang, Hanyin; Yi, Xin (Frontiers in Oncology, 2022)
Background The global gamma passing rate is the most commonly used metric for patient-specific pretreatment quality assurance in radiation therapy. However, the optimal region for evaluation and specific action limits (ALs) need to be explored. Therefore, this study was carried out to explore the optimal region for evaluation of the global gamma passing rate and define ALs by using the COMPASS software. Methods A total of 93 intensity-modulated radiation therapy (IMRT) plans for nasopharyngeal cancer (NPC) patients, including 61 original plans and 32 multileaf collimator (MLC) error-introduced test plans, were selected for retrospective analysis. Firstly, the dose distribution was divided into six isodose regions (“≥10%”, “≥20%”, “≥30%”, “≥40%”, “≥50%”, and “≥60%”) based on the prescribed dose and one clinically oriented region for evaluation (“whole”) to perform the three-dimensional (3D) global gamma reanalysis. Meanwhile, the percentage gamma passing rate (%GP), mean gamma index (μGI) based on 3%/2 mm criteria, and percentage dose error (%DE) of the dose–volume histogram (DVH) metrics were recorded by COMPASS application. Secondly, the Pearson’s correlation coefficient was used to analyze the correlation between %GP and %DE and between μGI and %DE in different regions. Additionally, receiver operating characteristic (ROC) methodology was applied to quantify the fraction of patient-specific plans evaluated as “fail” and “pass”. In order to improve the correlation between gamma analysis result and clinical criteria, ROC analysis was carried out in accordance with hybridization analysis criteria (%DE ≤3%, %GP ≥90% and %DE ≤3%, μGI ≤0.6). ROC was performed for two purposes: 1) to analyze the sensitivity and specificity of %GP and μGI in different regions for evaluation and 2) to define the ALs of %GP and μGI in the optimal region for evaluation. Finally, the plans introduced with MLC errors were prepared for validation. Moreover, we also compared the positive rate of ALs of both %GP and μGI in detecting MLC error-introduced plans in different regions. Results 1) In our study, a number of DVH-based metrics were found to be correlated with the evaluation parameters. The corresponding number was 4, 2, 1, 1, 1, 1, and 3 in γwhole, γ10%, γ20%, γ30%, γ40%, γ50%, and γ60%, respectively, and 5, 3, 0, 1, 1, 4, and 2 in μGIwhole, μGI10%, μGI20%, μGI30%, μGI40%, μGI50%, and μGI60%, respectively. The results by COMPASS have revealed that the %DE of specific structures has a slightly higher correlation with both %GP and μGI of the “whole” region compared with that of any other region. However, it is a moderate correlation (0.5 ≤ |r| < 0.8). 2) The areas under the curves (AUCs) of γwhole, μGIwhole, μGI40%, μGI50%, and μGI60% were >0.7 based on 3%/2 mm criteria. According to the Youden coefficient, we defined the ALs of γwhole ≥92%, μGIwhole ≤0.36, μGI40% ≤0.43, and μGI60% ≤0.40 based on 3%/2 mm criteria. 3) In the validation, for original plans, the accuracy of ALγwhole, ALγ10%, ALμGIwhole, ALμGI40%, ALμGI50%, and ALμGI60% was 23%, 9.8%, 90%, 80.3%, 9.8%, and 88.5%, respectively. For test plans with systematic MLC errors smaller than 0.8 mm, the positive rates of ALγwhole, ALγ10%, ALμGIwhole, ALμGI40%, ALμGI50%, and ALμGI60% were 25%, 58%, 92%, 92%, 42%, and 100%, respectively. For the plans with systematic MLC errors higher than 0.8 mm, the positive rates of all AL%GP and ALμGI were 100%. From the COMPASS validation results, the accuracy of γwhole, μGIwhole, μGI40%, and μGI60% was higher than that of the conventional γ10% and commonly used μGI50%. Conclusions Compared with the traditional evaluation region (i.e., the criteria with a threshold of 10% or a threshold of 50%, it was the same with the isodose regions of “≥10%”, “≥50%” based on the prescribed dose in our study), the “whole” region is more meaningful to the clinic by COMPASS. The accuracy of μGIwhole is higher than that of the conventional γ10% and the commonly used μGI50%.